Survival in patients with glioblastoma at a first progression does not correlate with isocitrate dehydrogenase (IDH)1 gene mutation status - Tabei, Yusuke (Jpn J Clin Oncol, 2020)
BACKGROUNDS: Mutations in the isocitrate dehydrogenase (IDH)1 gene are favourable prognostic factors in newly diagnosed diffuse gliomas, whereas it remains controversial in the recurrent glioblastoma setting. METHODS: A total of 171 patients with newly diagnosed glioblastoma, either ‘primary’ glioblastoma or ‘secondary’ glioblastoma, treated at Kyorin University Hospital or Japanese Red Cross Medical Center from 2000 to 2015 were included. Patients with confirmed IDH1 status and O(6)-methylguanine-DNA methyltransferase promoter methylation status were retrospectively analysed for overall survival from the initial diagnosis (n = 147) and after the first progression (n = 122). RESULTS: IDH1 mutation but not IDH2 was noted in 19 of 147 patients with glioblastoma (12.9%). In patients with ‘primary’ glioblastoma (n = 136), median overall survival after the first progression was 13.5 and 10.5 months for mutant IDH1 and wild-type IDH1 glioblastoma, respectively (P = 0.747). Multivariate analysis revealed O(6)-methylguanine-DNA methyltransferase promoter methylation, and Karnofsky Performance status 60 or higher, were independent prognostic factors for better overall survival after the first progression. When ‘primary’ glioblastoma and ‘secondary’ glioblastoma were combined, median overall survival from the first progression was not significantly different between the mutant IDH1 group (10.1 months) and wild-type IDH1 group (10.5 months) (P = 0.559), whereas median overall survival from the initial diagnosis was significantly different (47.5 months vs.18.3 months, respectively; P = 0.035). CONCLUSIONS: These results suggest that IDH1 mutation may not be a prognostic factor for survival at the first progression of patients with ‘primary’ glioblastoma and pretreated ‘secondary’ glioblastoma, and further warrant investigation in prospective studies.